modeling approach of return and volatility of structured investment products with caps and floors - Jiaer He; Roberto Rivera (Fórum Empresarial)
A popular investment structured product in Puerto Rico is the stock markettied Individual Retirement Account (IRA), which offers some stock market growth while protecting the principal. The performance of these retirement strategies has yet to be studied. This work examines the expected return and risk of Puerto Rico stock market IRAs (PRIRAs) and compares their statistical properties with other investment instruments after tax. We propose a parametric modeling approach for structured products and apply it to PRIRAs. Our method first estimates the conditional expected return (and variance) of PRIRA assets from which we extract marginal moments through the Law of Iterated Expectation. Our results indicate that PRIRAs underperform against investing directly in the stock market while carrying substantial risk. PRIRAs may be reasonable for some risk-averse investors due to their principal protection and tax deferral.